Pengaruh Harga, Kualitas Produk, Dan Electronic Word Of Mouth Terhadap Minat Beli Ulang Konsumen Pada Produk Kopi Keliling Merek Sejuta Jiwa Di Desa Wanajaya, Kabupaten Bekasi - Hamdi, Ferdiyan; Untari, Dhian Tyas; Rohaeni, Heni (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study aims to analyze the influence of Price, Product Quality, and Electronic Word of Mouth (e-WOM) on Repurchase Intention among consumers of the mobile coffee brand "Sejuta Jiwa" in Wanajaya Village, Bekasi Regency. A quantitative approach was applied using multiple linear regression analysis. Data were collected via online questionnaires distributed to 114 respondents who had purchased the product. The findings reveal that Price, Product Quality, and e-WOM each have a positive and significant partial effect on Repurchase Intention. Simultaneously, the three variables also show a significant combined influence on consumers' decisions to repurchase. These results emphasize the importance of appropriate pricing, consistent product quality, and managing consumer feedback through digital platforms in encouraging repeated purchase behavior.